1966
DOI: 10.1002/pol.1966.150041023
|View full text |Cite
|
Sign up to set email alerts
|

Studies of thermal cyclizations of polyamic acids and tertiary amine salts

Abstract: Thermal conversion rates of the polyamic acid derived from pyromellitic dianhydride and 4,4′‐diaminodiphenyl ether are presented. Formation of the imide ring proceeds by fast and slow first‐order processes. Tertiary amines give ring closures faster by a factor of 10 than the free acid. The enhancement is an activation entropy rather than an activation energy effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(115 citation statements)
references
References 6 publications
5
110
0
Order By: Relevance
“…The synthetic method of PI from pyromellitic dianhydride (PMDA) and 4,4'-oxydianiline (ODA) is shown in Scheme 1. Imidization of the PAA films is usually performed thermally, which needs high temperature (over 300 ºC) [4,5]. But, the high temperature often limits its application in many industrial fields.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic method of PI from pyromellitic dianhydride (PMDA) and 4,4'-oxydianiline (ODA) is shown in Scheme 1. Imidization of the PAA films is usually performed thermally, which needs high temperature (over 300 ºC) [4,5]. But, the high temperature often limits its application in many industrial fields.…”
Section: Introductionmentioning
confidence: 99%
“…Many early reports were rightfully concerned with studying both initial poly(amic acid) formation(1, 3) and imidization kinetics (4). The effect of temperature and residual water on poly(amic acid) solution stability was noted(1-3,5,6) and the potential for hydrolysis of both the poly(amic acid) and polyimide by water produced during imidization was speculated (3,6).…”
mentioning
confidence: 99%
“…The pathways of cyclization during thermal imidization suggested by Kreuz et al 17,18 are depicted in Figure 3. In In order to investigate the most plausible pathway for PI formation from PAA in the film state, the powerful 2D Raman correlation method was used to produce 2D Raman contour maps.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kreuz et al suggested that the proton attached to the nitrogen is lost either after or before cyclization. 17,18 They also suggested that the film type of PAA follows the former process, while deprotonation occurs first in basic solvents, such as N-methyl-2-pyrrolidone (NMP). Although their results are needed further confirmation, to our best knowledge, no studies have been performed.…”
Section: Introductionmentioning
confidence: 99%